1993
DOI: 10.1002/ijc.2910540616
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of mouse mammary carcinomas with vincristine and doxorubicin encapsulated in sterically stabilized liposomes

Abstract: This study tested the therapeutic effects of vincristine sulfate and doxorubicin hydrochloride, each drug in 2 different formulations: (i) as a solution in saline, and (ii) encapsulated in sterically stabilized, long-circulating liposomes composed of hydrogenated soy-phosphatidylcholine/cholesterol/polyethylene-glycerol-disteroyl++ +- phosphatidylethanolamine. The 4 drug preparations were used to treat s.c. implants of the mouse mammary carcinoma MC2. The drugs were given by i.v. injection over 15 to 18 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Results presented here as well as those of Vaage et al (37) suggest that coadministration of liposomal doxorubicin and liposomal vincristine results in less than additive activity or antagonism. In an effort to gain a better understanding about the cytotoxic effects of vincristine and doxorubicin when used in combination, in vitro cytotoxicity studies were completed using MDA435/LCC6 cells as the target cell population.…”
Section: Efficacy Of the Coencapsulated Liposomal Doxorubicin/ Vincrisupporting
confidence: 80%
See 2 more Smart Citations
“…Results presented here as well as those of Vaage et al (37) suggest that coadministration of liposomal doxorubicin and liposomal vincristine results in less than additive activity or antagonism. In an effort to gain a better understanding about the cytotoxic effects of vincristine and doxorubicin when used in combination, in vitro cytotoxicity studies were completed using MDA435/LCC6 cells as the target cell population.…”
Section: Efficacy Of the Coencapsulated Liposomal Doxorubicin/ Vincrisupporting
confidence: 80%
“…and liposomal doxorubicin did not provide improved therapy when simultaneously injected (37). Their results suggested that liposomal vincristine inhibited the activity of liposomal doxorubicin.…”
Section: Efficacy Of the Coencapsulated Liposomal Doxorubicin/ Vincrimentioning
confidence: 96%
See 1 more Smart Citation
“…Several reports have documented the ability of a variety of liposomes to decrease the toxicity and/or improve the efficacy of vincristine (Layton and Trouet, 1980;Mayer et al, 1990aMayer et al, , 1993Mayer et al, , 1995Vaage et al, 1993;Boman et al, 1994). Early studies revealed that vincristine is relatively permeable to the phospholipid membranes, a characteristic that limits the use of lipids containing unsaturated fatty acids, such as egg PC (Mayer et al, 1990a).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PEG modification avoids liposome aggregation improving stability of preparations. Vaage et al (1993) formulated vincristine-loaded PEGylated liposomes. Compared to SM/Chol liposomes, the particle size (about 100 nm) and trapping efficiency (495%) was similar to conventional liposomes, but the surface charges of these two formulations were different (the electrophoretic mobility of SM/Chol and PEGylated liposomes was 0.0 and À0.83 Â 10 À4 cm 2 /Vs) at pH 7.0 (Webb et al, 1998).…”
Section: Pegylated Liposomal Vincristinementioning
confidence: 99%